A dose response study of oxitropium bromide in chronic bronchitis. Issue 6 (June 1984) - Peel, E T; Anderson, G
Abstract : In a dose response study 12 patients with chronic bronchitis and airflow obstruction received inhaled placebo and incremental doses of oxitropium bromide. Significant improvements in peak expiratory flow rate, forced expiratory volume in one second, and forced vital capacity were recorded at all times up to 10 hours after all doses of oxitropium bromide. Oxitropium bromide is an effective bronchodilator in chronic bronchitis with an optimal dose of 400-600 micrograms.